PENGGUNAAN TANAH BENTONIT SEBAGAI ADSORBEN LOGAM Cu - Daniel S Bath, Jenal M Siregar, M Turmuzi Lubis (Universitas Sumatera Utara, 2012)
Bentonite serve the purpose of substance adsorpsi because swelling ability and cation for exchange. But adsorption ability is limited so that require to be activated by strong acid to higher level adsorption of bentonite. This research use Ca-Bentonit activated by strong acid HCl. Cation Cu analysed by using Spektofometri Serapan Atom (SSA). Result of research indicate that the increasing of HCl concentration and activation time can improve the adsorption capacity of bentonite. Maximum HCl concentration at 1,6 M and maximum activation time at 24 hour. Optimum heavy bentonite at 4 gr of 100 ppm Cu solution and optimum contact time at 2 hour. Result from Cu isoterm adsorption is weight of adsorption have same range with Cu concentration. Keywords : adsorption, bentonite, removal of Cu metal